Thermal Imaging in a Clinically Non-assessable Free Flap Reconstruction of the Face - Frohwitter, Gesche; Nobis, Christopher-Philipp; Weber, Manuel; Oetter, Nicolai; Rau, Andrea; Kesting, Marco Rainer; Lutz, Rainer (Plastic and Reconstructive Surgery Global Open, 2021)
Free flap monitoring and early detection of malperfusion are a central aspect in reconstructive surgery. Warm ischemia, measured as the time a certain tissue is able to survive without any additional medical or thermal treatment, ranges from hours in muscle and nerval tissue up to days in bony tissue. Hence, meticulous flap monitoring is essential to discover early signs of malperfusion and decide upon timely re-intervention. Besides clinical examination techniques and Doppler sonography, a multitude of mostly experimental procedures are available to evaluate free flap perfusion. Particularly in older patients, the assessment of the skin island in microvascular grafts is a demanding task because the natural loss of elasticity, the reduction of subcutaneous tissue, and the decrease in water content limit the visibility of capillary filling and favor hematomas. We report a case of a 90-year-old woman with an extensive cutaneous squamous cell carcinoma of the right zygomatic and lateral orbital region without any locoregional or distant metastasis. Due to the resilient health status, we decided for a surgical approach with consecutive microvascular radial forearm flap reconstruction. On account of the difficult assessment of elderly skin after microvascular transplantation, we decided on additional flap monitoring by thermal heat imaging during the operation and aftercare. This case report discusses the successful application of thermal heat imaging in a clinical non-assessable free flap and discusses the application of dynamic infrared thermography as a monitoring tool in microvascular free flap surgery.
CRIS-Team WoS Importer:2021-05-28